Swimming Pool Sanitation and the Health of Swimming Athletes in the Context of School Sports Education: A Systematic Review - Andi Tilka Muftiah Ridjal (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
Swimming is an essential component of school sports education that supports physical fitness, motor skill development, and lifelong health promotion. However, the effectiveness of swimming programs may be influenced by the sanitation quality of swimming pool environments. Poor swimming pool sanitation can increase the risk of microbial contamination, chemical exposure, and various health problems among swimmers, potentially affecting athlete participation and educational outcomes. This study aimed to systematically review the relationship between swimming pool sanitation and swimmer health within the context of school sports education. This study employed a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Literature searches were conducted in Scopus, Web of Science, PubMed, Google Scholar, and SINTA-indexed journals. Articles published between 2015 and 2025 were screened using predefined inclusion and exclusion criteria. Of the 247 records initially identified, 25 eligible studies were included in the final review. The findings revealed that microbiological contamination (92%), residual chlorine concentration (84%), and pH balance (80%) were the most frequently reported sanitation indicators. The most common health problems among swimmers were eye irritation (72%), skin disorders (68%), respiratory symptoms (60%), gastrointestinal complaints (48%), and ear infections (40%). Furthermore, 64% of studies reported reduced training attendance, while 56% identified decreased performance readiness associated with poor sanitation conditions. In conclusion, swimming pool sanitation is a critical determinant of swimmer health, training continuity, and educational effectiveness. Effective sanitation management is essential for ensuring safe aquatic environments and supporting sustainable athlete development within school sports education programs.